UJI COBA KEPRAKTISAN PENGEMBANGAN SOAL MATEMATIKA LEVEL 4 MODEL PISA MENGGUNAKAN KONTEKS COVID-19: TAHAPAN SMALL GROUP - Reihani, Maha; Efriani, Arvin (Epsilon: Jurnal Pendidikan Matematika, 2021)
continuing the previous article about creating and developing PISA model math problems using the context of everyday life which aims to build students’ thinking in solving these problems. While the author’s purpose of doing this research is to produce valid and practical mathematical problems. The research in this article involves six students of a public junior high school in Palembangas the subject of a small group research. The research method used is design research type development study. Data collection techniques consist of documentation, walk-through, tests, and interviews. The question developed is a continuation of the previous article, namely one level four item. The results are the study stated that the developed question was valid and practical as seen from the student who were able to understand the meaning of the question, make assumptions and make related settlement plans so that they could produce the correct answer.